Long Island Sound Prospects for the Urban Sea - Latimer, James S.; Tedesco, Mark A.; Swanson, R. Lawrence; Yarish, Charles; Stacey, Paul E.; Garza, Corey; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Long Island Sound: Prospects for the Urban Sea is the first synthesis of the science of Long Island Sound in more than thirty-five years. Described by Daniel Webster as the American Mediterranean, four centuries of human habitation, use, and abuse have created a trajectory of change being duplicated in estuaries throughout the country. Now subject to coordinated restoration efforts, the fate of Long Island Sound is a harbinger of the fate of coastal waters and economies everywhere.   Six technical chapters summarize our knowledge about the human history, geology, physical oceanography, geochemistry, pollutant history, and biology and ecology of Long Island Sound. The last chapter identifies the linkages between science and environmental management, drawing extensively from hard-learned lessons on identifying threats and implementing strategies to confront them. This synthesis will be of interest to anyone engaged in the conservation and restoration of coastal ecosystems: scientists, students, managers, planners, and environmentalists. “This massive, multidisciplinary synthesis is a welcome contribution to the understanding of Long Island Sound, providing not only new knowledge, but important information relevant to managers of coastal ecosystems. It will provide an extremely valuable resource for Long Island Sound for many years to come.” Gene E. Likens Founding Director and President Emeritus Cary Institute of Ecosystem Studies, Millbrook, NY “Long Island Sound: Prospects for the Urban Sea" is a major new and timely contribution to the literature on one of the nation’s most important estuaries. Prospects for all our estuaries are changing, primarily as a result of coastal development and effects associated with climate change particularly sea level rise and increased power of storm surges, rising temperatures and ocean acidification. This book provides valuable insights into understanding these impacts and into how to improve the prospects for the qualities and uses of Long Island Sound most important to society and to creating and maintaining a healthy, productive ecosystem. Many of the lessons are transferrable to other estuaries and coastal systems.” Jerry R. Schubel President and CEO Aquarium of the Pacific, Long Beach, California  .
Dedication -- Preface/Introduction -- Acknowledgements -- Contributors -- Acronyms and Common Units -- Chapter 1: LONG ISLAND SOUND: A SOCIOECONOMIC PERSPECTIVE -- Chapter 2: THE GEOLOGY OF LONG ISLAND SOUND -- Chapter 3: THE PHYSICAL OCEANOGRAPHY OF LONG ISLAND SOUND -- Chapter 4: GEOCHEMISTRY OF THE LONG ISLAND SOUND ESTUARY -- Chapter 5: METALS, ORGANIC COMPOUNDS, AND NUTRIENTS IN LONG ISLAND SOUND: SOURCES, MAGNITUDES, TRENDS AND IMPACTS -- Chapter 6: BIOLOGY AND ECOLOGY OF LONG ISLAND SOUND -- Chapter 7: SYNTHESIS FOR MANAGEMENT -- Glossary.-.
Keywords: Aquatic ecology .; Hydrology; Marine sciences; Freshwater; Ecosystems; Environmental management; Conservation biology; Ecology .; Freshwater & Marine Ecology; Hydrology/Water Resources; Marine & Freshwater Sciences; Ecosystems; Environmental Management; Conservation Biology/Ecology.